A Covid19 a természet reneszánsza - Bendes , Ákos (Kultúratudományi Szemle, 2022)
Covid19 is a renaissance of nature Ákos Bendes The newly emerged pandemy sheds light on many issues ranging from fragility of our supply chains to economic depression, and all of them have ethical dimensions. To be more precise, we need to clarify the exact nature of a just conduct in the situations arising from crisis. However, the appealing consequentialist theories usually fall short of meeting a fundamental principle, namely the criterion of equal treatment. In the twentieth century, the hegemony of utilitarism started to decline because of the appearance of more sophisticated views. These theories are trying to reconcile the idea of equal moral worth with utilitarist considerations.